(untitled) (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2022)
This research aimed to determine the effect of engaging leadership on work engagement with positive affect as a mediating variable on Islamic Bank employees in Medan City. This study used a quantitative method using questionnaires and involved 100 Islamic Bank employees in Medan City. There are three measuring tools used in this study, namely variables measuring engaging leadership scale (ELS), Utrecht Work Engagement (UWES) and Positive and Negative Affect Schedule (PANAS). The data obtained were processed using IBM Statistical Product and Service Solution (SPSS) and hypothesis testing by WarpPLS 7.0. The results showed that positive affect had a role as a mediator in the relationship between engaging leadership and work engagement for Islamic Bank employees in Medan City (p = 0.000 < 0.05).